2019
DOI: 10.21203/rs.2.12461/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inappropriate child feeding practice and primary health care as major correlates of stunting and underweight among infants and young children 6-23months of age in food insecure households of Amhara and Oromia Regions, Ethiopia. A community based cross sectional study

Abstract: Background: Child undernutrition is a major public health problem in Ethiopia. Even though the highest levels of stunting are found in food insecure areas, insufficient evidence limits effective intervention to improve the situation. Therefore, this study aimed to assess undernutrition and associated factors among infants and young children aged 6–23 mo in food insecure households of Amhara and Oromia Regions, Ethiopia. Method: A community based cross-sectional study was conducted in productive safety net targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Moreover, those studies also showed the chances of a child being stunted increase as they get older. This has been mainly explained by poor child feeding practice (37,38) and more exposure to environmental enteropathy accompanied by diarrhoea (22,39) . In the present study, the association might be influenced by the high performance (94⋅2 %) of vaccination (31) in the city that enables the children to cope with some enteric pathogens (40,41) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, those studies also showed the chances of a child being stunted increase as they get older. This has been mainly explained by poor child feeding practice (37,38) and more exposure to environmental enteropathy accompanied by diarrhoea (22,39) . In the present study, the association might be influenced by the high performance (94⋅2 %) of vaccination (31) in the city that enables the children to cope with some enteric pathogens (40,41) .…”
Section: Discussionmentioning
confidence: 99%